Institutional impacts on the resilience of mountain grasslands: an analysis based on three European case studies. (March 2016) - Schermer, Markus; Darnhofer, Ika; Daugstad, Karoline; Gabillet, Marine; Lavorel, Sandra; Steinbacher, Melanie
Abstract: Over the centuries, specific farming practices shaped permanent grasslands in mountains. With socio-economic change, farming practices have changed and with them the landscape. Over time, food production has been increasingly decoupled from the preservation of permanent grassland, endangering the delivery of crucial ecosystem services. This contribution looks into the role of institutions – including normative, regulative and cultural-cognitive elements – in preserving current bundles of ecosystem services provided by mountain grasslands. In particular, we investigate how such institutions affect farmers' management choices. Based on a review of scientific literature and empirical data from three case studies, we compare institutions in Austria, France and Norway. The cases represent different modes of multi-level governance (EU and non-EU), different grassland management practices, linked to different farming systems (dairy, breeding, rearing of heifers, suckler cow and sheep production) and different socio-economic conditions. The results underpin that ecological insights into the impact of farming practices on the ecology of grassland need to be combined with an understanding of the complex institutional interactions that affect farming practices, to ensure the resilience of mountain grasslands. If the design of regulatory measures considers both changing dynamics, it may enable farms to adapt and transform while maintaining traditional grassland management practices